Digital Twins and Democracy - Calvo, Patrici (Revista del CLAD Reforma y Democracia, 2022)
The aim of this study is to critically analyze the challenges and possibilities underlying the application of participatory processes based on artificial intelligence algorithms in politics. It will focus on the proposal of augmented democracy which is being designed and developed from different technological and academic fields based on digital twins and design principles. Currently, the disaffection of citizens in the different political processes, such as the drafting of laws and the implementation of strategies and public policies, and the inability of political representatives to fully absorb the voice of the citizens, has become a burden for the development of modern societies. In response to such social and political challenges, the academic and technological world has come up with participatory proposals such as augmented democracy that raise the possibility of adapting and applying technology from the productive industry: digital twins.
Keywords: Ethics; Democracy; Citizen Participation; Cybernetics; Artificial Intelligence; Digital Social Networks